Application of high-thermal-conductivity diamond for space phased array antenna. Issue 1 (14th January 2022) - Lu, Wei; Li, Jin; Miao, Jianyin; Chen, Liangxian; Wei, Junjun; Liu, Jinlong; Li, Chengming
Abstract: Active phased array antenna typically featured high performance, high device integration, and high heat flux, making it difficult to dissipate heat. Diamond, the substance with the closest arrangement of atoms in nature, has the advantages of a high thermal conductivity and strong adaptability to the space environment. The batch applications of high-thermal-conductivity diamonds for the thermal management of the phased array antennas of the inter-satellite links were introduced in this paper. The diamond was developed by the direct-current arc-plasma chemical vapor deposition method. The product size, thermal conductivity, precision, and application scale all met the engineering requirements. The high-precision assembly of the diamond and the structural frame enabled the efficient heat collection and transfer from the distributed point heat sources of multiple transmit/receive (T/R) modules. Verified on the ground, the thermal matching design between the diamond and the metal frame exhibited an outstanding heat dissipation performance. After four satellites using the diamonds were launched, the flight data showed good antenna thermal control, with temperature gradients of the T/R modules less than 2.2 °C, further verifying the rationality and effectiveness of using high-thermal-conductivity diamonds in the thermal design and implementation of antennas.